The contribution of philanthropic organizations to collection development in Nigeria acedemic libraries (2008)
Discusses the contribution of philanthropic organizations to collection development in libraries in South Western Nigeria. Questionnaires, structured interview, and observation methods were used in gathering the required data. Using random sampling techniques, five tertiary institutions were selected from the seventeen in the Southwest. The study reveals that book donations from philanthropic organization have positive impact on collection development by increasing the volumes of books in their collection. It was also discovered that the major donor to the libraries was Book Aid International and that the books donated sometimes do not cut across all disciplines. Acquisition by purchase is not seriously affected by the donations as the libraries continue to acquire in spite of outside help. It is recommended that the donors in a way involve the receiving or benefiting universities in the selection exercise so as to meet the desired needs of the institutions.